PROFIL PERENCANAAN KARIR SISWA DI ERA PANDEMI COVID-19 DAN IMPLIKASINYA BAGI PROGRAM BIMBINGAN KARIR - Desi Nurfitria; Raudah Zaimah Dalimunthe; Bangun Yoga Wibowo (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2021)
The research was motivated by the existence of career planning problems for students at SMA Negeri 6 Serang City. The purpose of the study was to see the level of student career planning during the covid-19 pandemic, then to design a program to improve student career planning, especially students of class XI SMA Negeri 6 Serang City. The type of research used is descriptive research. The population in this study were all students of class XI SMA Negeri 6 Serang City with a research sample of 205 students. The data collection technique used is by spreading the research instrument in the form of a questionnaire with 31 valid items, the reliability value obtained is 824. While the technical analysis of the data used is descriptive quantitative. The results showed that the level of career planning during the covid-19 pandemic experienced by class XI students of SMA Negeri 6 Serang City was in the medium category with a percentage of 82%. Then the program design is made according to the needs that are known from the research results that have been obtained.